Exploring Qualities that Prevent EFL Teachers from Redundancy - I Dewa Gede Rat Dwiyana Putra; Sayit Abdul Karim; Iswandany Kaslan (Register Journal, 2023)
The practice of English language teaching has dramatically changed with the existence of Internet-based learning platforms. The educational technology provides EFL students with a variety of language learning materials that can be accessed at any time and anywhere. These phenomena might threaten the teacher's existence. Thus, this study aims to figure out whether or not EFL teachers’ roles can be replaced by technology and to explore what qualities they should possess and maintain to prevent them from redundancy due to the domination of mobile-based language learning applications. A mix-method design was utilized to obtain the quantitative data through an online survey and qualitative data through an open-ended question. 199 EFL learners participated in the online survey, which consisted of a yes/no question on whether teachers could be replaced by mobile apps and an open-ended question to record the reasons. The findings showed that 132 students (66.3%) thought that teachers could not be replaced by mobile technology; meanwhile, around one-third of the respondents, 67 students (33.7%) had the opposing thought. The students still require human interaction, a sense of emotion, and delivery over the mobile tech features that could provide availability, flexibility, and practicality. It is highly recommended that English teachers maintain their humane qualities while keep adapting to technology to save themselves from redundancy.